Efektifitas Permit to Work dalam Mengurangi Occupational Accident di Kapal MT Pangalengan - Setyoati, Estri; Suwondo, I'ie; Dahri, Muhammad; Haryanto, Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to find out the causes of the lack of effectiveness of Permit to Work on MT ships. Pangalengan, then this study also seeks to find out how efforts to make Permit to Work effective in reducing occupational accidents on MT ships. Pangalengan, and finally to find out the impact of the less effective Permit to Work. The research method used is descriptive qualitative research to describe a complex picture based on findings from direct reports, secondary sources, and statistical analysis, as well as information collected from interviews and other sources. The results of the study show that the common factors causing the ineffectiveness of permits to work on MT ships. Pangalengan is the lack of understanding of the crew related to the procedures and implementation of permits to work on board MT ships. Pangalengan. The effectiveness of permits to work can be increased by providing adequate knowledge and training to crews, as well as increasing their motivation. Failure to implement an effective permit to work system can lead to work accidents that have the potential to endanger worker safety.